Effects of different variables on moisture transfer of household refrigerator-freezer - Hasanuzzaman, M.; Saidur, Rahman; Masjuki, Haji Hassan (Sila Science, 2011)
Moisture transfer plays an important role in the hot and humid climate like Malaysia to preserve perishable food in the refrigerator-freezer. This paper presents the moisture transfer of household refrigerator-freezer during the open and closed door conditions. Experiments were conducted in the controlled chamber to investigate the effects of the different variables on moisture transfer. When the refrigerator-freezer door is opened, the moist warm ambient air enters into the cooler cabinets. The warm moisture gets cool and forms ice. On the other hand, during the defrosting system, the ice is warm up and defrosted. The energy is needed to form ice and defrost ice that is increased the energy consumption of refrigerator-freezer. Moisture transfer is greatly influence by the number of door opening, ambient temperature and water pan area.